Pilot Plant Production of Medium Filter for Seed Testing - Sharma, Y. K. (Indian Forester, 1970)
Pilot plant scale trials on production of medium filter for seed testing are described. This variety of speciality paper is at present being imported. The important characteristics of this paper are an open, porous formation; freedom from fungi or bacteria that might interfere with the growth of germinating seedlings; freedom from toxic substances; and satisfactory strength properties especially wet strength.